Factors associated with colostrum immunoglobulin G concentration in northern‐Victorian dairy cows. Issue 7 (July 2017) - Phipps, AJ; Beggs, DS; Murray, AJ; Mansell, PD; Pyman, MF
Abstract : Objectives: To determine the proportion of first‐milking colostrum samples produced on four northern‐Victorian dairy farms that meet industry standards in terms of immunoglobulin G (IgG) concentration and to identify risk factors that affect colostrum quality. Methods: Colostrum IgG concentrations from 442 dairy cows on four farms were estimated using a Brix refractometer and risk factors for colostrum IgG concentration were determined using multivariable logistic regression. Results: Only 39% of samples met the definition of high quality. The strongest predictor for colostrum quality was the interval from calving to colostrum harvesting. Colostrum harvested from cows within 12 h of calving was 6‐fold more likely to be high quality compared with colostrum harvested later. Colostrum from cows in ≥ 4th lactation was nearly twice as likely to be high quality compared with cows entering their 1st lactation. If the calf was not allowed to suckle from the dam prior to colostrum harvesting, the odds of producing high‐quality colostrum were nearly 4‐fold greater. If the cow had not leaked colostrum prior to harvesting, it was more than 3‐fold more likely to produce high‐quality colostrum. Conclusions: The majority of samples assessed were below industry standard. Herd, lactation number, calf suckling or cow leaking colostrum prior to harvesting and time between calving and colostrum harvesting were factors that influenced colostrum IgG concentration. The results support current industry recommendations of harvesting colostrum shortly after parturition (ideally within 12 h of calving) and testing the quality of all colostrum prior to feeding to dairy calves.